Bio-upcycling of cheese whey: Transforming waste into raw materials for biofuels and animal feed - Valeria Caltzontzin-Rabell; Ana Angélica Feregrino-Pérez; Claudia Gutiérrez-Antonio (Heliyon, 2024)
Cheese whey (CW), by-product of cheese production, has potential as a valuable resource due to its nutritional composition. Although options for CW degradation have been explored, a biological treatment with black soldier fly larvae (BSFL) has not been reported. This study evaluated the growth and composition of BSFL in four experimental diets with CW under different conditions. Results show that the use of CW allows larval development and weight gain, also, the conversion into larval biomass was up to 0.215. Diets ED3 (fresh CW, 38 °C) and ED4 (fresh CW, room temperature) allowed higher weight accumulation (final weight up to 0.285 g); the highest fat accumulation (12 % higher than control) was observed in ED3 (up to 45.57 %), which had less protein. Moreover, higher amounts of saturated fatty acids are generated. This study highlights the importance of an appropriate pretreatment designed for a specific waste to control desired by-products.